2019
DOI: 10.1016/j.jpha.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

FITC labeling of human insulin and transport of FITC-insulin conjugates through MDCK cell monolayer

Abstract: Fluorescein isothiocyanate-labeled insulin (FITC-insulin) has been widely used for bioanalytical applications. Due to the high cost of commercial FITC-insulin and tedious labeling procedures described in the literature, there is still a need to develop a cost effective, reliable and quick labeling method for insulin. The purpose of the present work was to develop a quick and affordable method for FITC labeling of human insulin and to determine the effect of different conjugations of FITC to human insulin on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Besides, to further confirmed the immobilization of alcalase, alcalase@HMSS-NH 2 -Fe 3+ was fluorescently labeled by FITC, and an extensive dialysis was performed until no release of free FITC into solution. FITC is an amine reactive fluorescent probe which labels protein by forming a covalent bond between its isothiocyanate group and the primary and secondary amine groups of lysine (Shah et al, 2019). As shown in Figure S2, the distinct green fluorescence in CLSM image of alcalase@HMSS-NH 2 -Fe 3+ provided a persuasive confirmation for the successful immobilization of alcalase.…”
Section: Characterization Of the Hmss Carriers And Immobilized Alcalasementioning
confidence: 89%
“…Besides, to further confirmed the immobilization of alcalase, alcalase@HMSS-NH 2 -Fe 3+ was fluorescently labeled by FITC, and an extensive dialysis was performed until no release of free FITC into solution. FITC is an amine reactive fluorescent probe which labels protein by forming a covalent bond between its isothiocyanate group and the primary and secondary amine groups of lysine (Shah et al, 2019). As shown in Figure S2, the distinct green fluorescence in CLSM image of alcalase@HMSS-NH 2 -Fe 3+ provided a persuasive confirmation for the successful immobilization of alcalase.…”
Section: Characterization Of the Hmss Carriers And Immobilized Alcalasementioning
confidence: 89%
“…[68] Site-specific incorporation of amine-reactive fluorescent molecules into insulin has been mostly achieved through attachment to primary amines A1 (Gly), B1 (Phe) and the ε-amino group of B29 (Lys). The order of reactivity of these amines was found to be B1 > A1 > B29; it has been shown that mono-conjugates of insulin labelled at B1 can be obtained by carefully controlling the labelling conditions, [69] and that B1 conjugates have the same biological activity as native insulin. [70] Thus, examination of Zn 2+ -induced insulin com-plexation, and subsequently, HSA-mediated decomplexation using HSA preparations containing different concentrations of NEFAs, should be possible using fluorescent mono-conjugates of insulin if a method can be developed where the fluorescent properties change upon complexation/decomplexation.…”
Section: Establishing the Role Of Nefas In Insulin Decomplexation Using Fluorescence-based Methodsmentioning
confidence: 99%
“…In the case of human insulin (Figure 4), the amino groups are 1 Gly in the A-chain and 1 Phe, 22 Arg, and 29 Lys in the B-chain. The reactivity of 1 Phe in the B-chain is the highest among the amino groups of insulin [45]. The hydroxyl groups are 9 Ser, 14 Tyr, and 19 Tyr in the A-chain and 9 Ser and 27 Thr in the B-chain.…”
Section: Design Of Intranasal Insulin Conjugates With Low Molecular Amentioning
confidence: 98%
“…Furthermore, the membrane permeability made a difference depending on the degree of FITC conjugate to insulin. The rank order of the permeability through the Madin-Darby canine kidney cell (MDCK) monolayer was mono-conjugate > unlabeled insulin > tri-conjugate [45]. Tri-conjugate is more hydrophobic than insulin.…”
Section: Intranasal Insulin Trajectory To the Brain After Crossing Thmentioning
confidence: 99%